Characterization Shift Through the Use of Affect in “Boys Don’t Cry” - Anida Khoirulnisa (Jurnal Bahasa, Sastra, dan Studi Amerika, 2025)
This study looks at how the protagonist and antagonist characters in the novel "Boys Don't Cry" employ affect, as well as the characterization that results.  The purpose of this study is to examine the forms of affect employed by the characters, as well as the characterization manifested, and to explain how the usage of affect and characterization evolved based on the narrative text's general structure.  This study used descriptive qualitative research with embedded single case study.  To achieve the objectives, this study employs appraisal framework and characterization theory.  The research location takes the form of a novel entitled "Boys Don't Cry". The findings revealed 278 applications of affect, the majority of which were negative-antipathy affect.  The findings also indicate that affect influences character characterization, with negative-irritable characterization being the most prevalent attribute.  Furthermore, it was discovered that the usage of affect evolves based on the narrative text's general structure, which determines the development of characterization.